Effects of different intensities of exercise on folliculogenesis in mice: Which is better? - Rahayu, Fitri Kurnia (Clin Exp Reprod Med, 2021)
OBJECTIVE: Exercise is a risk factor for infertility in women. However, research on the effects of different intensities of exercise on folliculogenesis has not yielded clear results. This study was conducted to analyze the effects of differences in the intensity of exercise on folliculogenesis in mice. METHODS: Nineteen female BALB/c mice (age, 3–4 months; weight, 13–25 g) were randomly divided into four groups: control, mild exercise, moderate exercise, and high-intensity exercise. The mice in the exercise groups engaged in swimming, with additional loads of 3%, 6%, or 9% of body weight, respectively. There were five swimming sessions per week for 4 weeks, with a gradually increasing duration every week. At the end of the treatment, ovarian extraction was carried out and hematoxylin and eosin staining was performed to identify folliculogenesis. RESULTS: There were significant differences in the number of total follicles between the control and moderate-exercise groups (p=0.036) and between the mild- and moderate-exercise groups (p=0.005). The mean number of primary follicles was higher in the moderate-exercise group than in the mild-exercise group (p=0.006). The mean number of secondary, tertiary, and Graafian follicles did not differ significantly among groups (p≥0.05). However, the number of total follicles and follicles in each phase tended to increase after exercise, especially moderate-intensity exercise. CONCLUSION: Exercise of different intensities affected the total number of follicles and primary follicles. The number of follicles of each phase tended to increase after exercise. Moderate-intensity exercise had better effects than other intensities of exercise.